Daily walking time effects of the opening of a multifunctional facility “ONIKURU” using propensity score matching and GPS tracking techniques - Haruka Kato (Scientific Reports)
Abstract Urban design focused on improving walkability has received attention as a method of increasing physical activity among the population. However, only a few studies have examined the effect of walking time of opening multifunctional facilities as an architecture-scale intervention. This study aimed to clarify the effect of opening a multifunctional facility on residents’ daily walking time. In addition, this study analyzed the gender and age subgroups. The natural experiment was conducted using the case of the Ibaraki City Cultural and Childcare Complex “ONIKURU,” a public multifunctional facility. This study used GPS-trajectory data based on GPS tracking techniques, which is anonymized location data for smartphone users. The causal relationship was analyzed using propensity score matching and difference-in-differences analysis. The results showed that the opening of ONIKURU significantly increased the average walking time of visitors to 3.165 [− 1.697, 8.027] min/day compared with that of non-visitors. Specifically, visitors’ average daily walking time improved to a level comparable to that of non-visitors after the opening of ONIKURU. In addition, opening ONIKURU significantly increased female young adults’ average walking time to 3.385 [− 4.906, 11.676] min/day. Therefore, this study provides theoretical contributions to a health-promoting built environment significantly affecting walking at an architecture-scale intervention.